CHanging notions of public accountability - Reid, William K
The author discusses that this article has commented briefly on some recent developments and changes observed in public structures and accountability. I emphasize the need for public administrators to improve their communication skills, to listen to the public, to minimize delay, to give reason for their actions, to be responsive to audit whether financial or quality, to concede that appeals on decisions are openly fairer when decided by an external agency properly trained and aware of its own responsibilities to set and explain their aims and objectives. If they do all these thins, they may be less likely to come athwart either the courts or ombedsmen
Keywords: Administrative Responsibility; Ombudsman